The Application of Continuous Mining Machines at Coalbrook Collieries - R. E. Burnton; J. G. Ferguson (The Southern African Institute of Mining and Metallurgy)
The nature of the coal and of the roof in No. 3 seam at Coal brook Collieries is such as to preclude the use, during bord and pillar mining, of conventional mining equipment that employs cutting and blasting in its production cycle. Continuous mining machines of the borer type, operating within a mining height range of 1,9-2,3 m, have been successfully employed in No. 3 seam since 1957.The experience gained with this type of equipment, the operational methods adopted, and the results achieved are described. The ventilation method used to eliminate the dust and methane hazards created by this type of equipment is stressed. The limitation on the minimum mining height that can be obtained with the borers in use has lead to the recent introduction of a Rotary Drum type of continuous mining machine. This equipment is capable of operating in areas where the seam width decreases to 1,5m. The production potential of the machine has been proved. The roof conditions created by the cutting action of the Rotary Drum type of miner are not considered satisfactory and a modified drum head profile is to be tried.